Growth and poverty reduction in Pakistan - Saeed, Wajiha; Davies, Stephen (International Food Policy Research Institute, 2018)
Over the last two decades, Pakistan has made significant progress in reducing all measures of poverty. The consumption-based poverty headcount decreased from 57.9% in 1998-99 to 29.5% in 2013-14, while the incidence of multidimensional poverty has declined from 55.2% in 2004-05 to 38.8% in 2014-15. However, as noted by the World Bank and the 2015-16 Economic Survey from the Ministry of Finance, much of the population remains in poverty or could fall into poverty if economic conditions worsened. Simultaneously, measures of inequality have risen. In comparison to 1987-88, the richest 20% now consume seven times more than the poorest 20%, and, while multidimensional poverty is less than 10% in major cities, it is more than 90% in some districts. Furthermore, Pakistan has experienced structural changes such that the share of services in total GDP has grown considerably. Agriculture’s contribution to GDP declined from 22.9% to 18.9%2 over the period 2003-04 to 2017-18. Yet, the labor force is still employed in agriculture, as its share in total employment has only seen a marginal decline, from 43.1% in 2003-04 to 42.3%.